Pathophysiology and consequences of arterial stiffness in children with chronic kidney disease - Azukaitis, Karolis; Jankauskienė, Augustina; Schaefer, Franz; Shroff, Rukshana (Pediatric neurology, 2021)
Changes in arterial structure and function are seen early in the course of chronic kidney disease (CKD) and have been causally associated with cardiovascular (CV) morbidity. Numerous potential injuries encompassing both traditional and uremia-specific CV risk factors can induce structural arterial changes and accelerate arterial stiffening. When the buffering capacity of the normally elastic arteries is reduced, damage to vulnerable microcirculatory beds can occur. Moreover, the resultant increase to cardiac afterload contributes to the development of left ventricular hypertrophy and cardiac dysfunction. Adult studies have linked arterial stiffness with increased risk of mortality, CV events, cognitive decline, and CKD progression. Pulse wave velocity (PWV) is currently the gold standard of arterial stiffness assessment but its measurement in children is challenging due to technical difficulties and physiologic aspects related to growth and poor standardization between algorithms for calculating PWV. Nevertheless, studies in pediatric CKD have reported increased arterial stiffness in children with advanced CKD, on dialysis, and after kidney transplantation. Development of arterial stiffness in children with CKD is closely related to mineral-bone disease and hypertension, but other factors may also play a significant role. The clinical relevance of accelerated arterial stiffness in childhood on cardiovascular outcomes in adult life remains unclear, and prospective studies are needed. In this review we discuss mechanisms leading to arterial stiffness in CKD and its clinical implications, along with issues surrounding the technical aspects of arterial stiffness assessment in children.